ANALISIS PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN PUSAT BIAYA GUNA MENINGKATKAN KINERJA MANAJER PT. TRIMITRA SWADAYA MEDAN - Zuliana Zulkarnen; Jesica Br Ginting (UNIVERSITAS DHARMAWANGSA, 2022)
The purpose of this study is to identify and analyze the use of responsibility accounting in assessing the performance of cost center managers and to find out the cause of the realization that the results obtained are not in accordance with the company's budgeted targets. Meanwhile, the formulation of the problem in this research is why there is a large adverse difference?, and whether responsibility accounting has been used as a tool for assessing the performance of cost center managers at PT. Trimitra Swadaya Medan?. The data collection technique used in writing this thesis is a study of documentation and interviews, while the data analysis technique used is descriptive analysis method. Based on the results of the study, it can be concluded that the use of cost center responsibility accounting information in evaluating the performance of managers at PT. Trimitra Swadaya Medan is still not implemented optimally, it is known that there is still a large difference between the realization and the budget from 2015 to 2020, which ranges from 2.04% to 25.14%. In addition, the cost center responsibility accounting in assessing the performance of managers at PT. Trimitra Swadaya Medan is still not implemented optimally where the overall expenditure from 2015 to 2020 turns out to provide expenses that are not on target for the company.